Dinamika Kesiapan Mental Ibu Remaja sebagai Orang Tua Baru dan Implikasinya terhadap PAUD: The Dynamics of Mental Readiness of Teenage Mothers as New Parents and Its Implications for Early Childhood Education - Sevtya Sya’bana Harun; Esya Anesty Mashudi (Universitas Ngudi Waluyo, 2026)
This descriptive qualitative study aims to understand the dynamics of young mothers' mental readiness in carrying out their duties as new parents, as well as to identify the psychological, emotional, and social challenges in caring for young children. This method applies purposive sampling to mothers G (aged 20 years, married under 19 years, married for more than 2 years) in Tangerang Regency, Kelapa Dua District, using semi-structured interviews and non-participant observation. The results of the study show ambivalent emotions after childbirth (such as baby blues and stress), a gradual mental preparation process, a busy daily routine with challenges such as children's tantrums, support from close family that conflicts with social pressure from the environment, a permissive parenting approach accompanied by basic stimulation at home, and diverse experiences with early childhood education that require inclusive strategies. Through Miles & Huberman's analysis, this study produced recommendations for family-oriented Holistic Integrative PAUD through thematic parenting programs, reflective interactions between teachers and parents, and intersectoral policies to reduce parenting stress and improve the quality of childcare by adolescent mothers, which addresses the issue of the impact of early marriage on mental preparation and its implications for PAUD. ABSTRAK Penelitian kualitatif deskriptif ini bertujuan untuk memahami dinamika kesiapan mental ibu muda dalam melaksanakan tugas sebagai orang tua baru, serta mengenali tantangan psikologis, emosional, dan sosial dalam merawat anak usia dini. Metode ini menerapkan purposive sampling pada ibu G (berusia 20 tahun, menikah di bawah 19 tahun, pernikahan selama 2 tahun lebih) di Kabupaten Tangerang, Kecamatan Kelapa Dua dengan menggunakan wawancara semi-terstruktur dan observasi nonpartisipan. Hasil penelitian menunjukkan adanya emosi ambivalen pasca melahirkan (seperti baby blues dan stres), proses persiapan mental yang bertahap, rutinitas harian yang padat dengan tantangan seperti tantrum anak, dukungan dari keluarga dekat yang bertentangan dengan tekanan sosial dari lingkungan, pendekatan pengasuhan yang permisif disertai stimulasi dasar di rumah, serta pengalaman dengan PAUD yang beragam yang memerlukan strategi inklusif. Melalui analisis Miles & Huberman, penelitian ini menghasilkan saran untuk PAUD Holistik Integratif yang berorientasi pada keluarga melalui program parenting tematik, interaksi reflektif antara guru dan orang tua, serta kebijakan antarsektor guna mengurangi stres parenting dan meningkatkan mutu perawatan anak oleh ibu remaja, yang menjawab permasalahan dampak pernikahan dini pada persiapan mental serta implikasinya terhadap PAUD.